2021
DOI: 10.3389/fcell.2021.724837
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of m6A Regulator-Mediated RNA Methylation Modification Patterns and Immune Characteristics in Lupus Nephritis

Abstract: BackgroundThere is growing evidence to demonstrate that the epigenetic regulation of immune characteristics, especially for N6-methyladenosine (m6A) RNA methylation. However, how m6A methylation is involved in lupus nephritis (LN) is still unclear. This study aimed to determine the role of m6A RNA methylation and their association with the immune microenvironment in LN.MethodsIn total, 87 glomeruli (73 LN, 14 living healthy donors), 110 tubulointerstitium (95 LN, 15 living healthy donors), and 21 kidney whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Various studies have confirmed that this strategy is feasible. For non-tumor diseases, several studies have applied this clustering method to study the impact of the immune microenvironment on disease ( Zhang et al, 2021 ; Zhao et al, 2021 ). For tumors, one study divided gastric cancer into three patterns and demonstrated the impact of the tumor microenvironment on the disease, which offered new ideas for immunotherapy ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have confirmed that this strategy is feasible. For non-tumor diseases, several studies have applied this clustering method to study the impact of the immune microenvironment on disease ( Zhang et al, 2021 ; Zhao et al, 2021 ). For tumors, one study divided gastric cancer into three patterns and demonstrated the impact of the tumor microenvironment on the disease, which offered new ideas for immunotherapy ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…m 6 A has a broad range of functions in organ development and disease processing ( 22 , 23 ). Several studies have delineated the regulation mechanism of m 6 A modification in glomerulopathy and renal fibrosis ( 16 , 24 ). Thus far, few studies have investigated the involvement of m 6 A in kidney and ureter development.…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylated genes were significantly involved in immune-related and inflammatory pathways, including interferon signaling [36], which is central to the pathogenesis of SLE [37]. A distinct regulation pattern of mRNA modifier, N4-acetylcytidine (ac 4 C) [38] and N6-methyladenosine (m 6 A) [39] has been observed in lupus and lupus nephritis, respectively, but the direct link with disease pathology has not been established. More studies are needed to relate this apparent correlation between RNA methylation and SLE to specific outcomes or signaling pathways in the pathology of SLE.…”
Section: T-cell Epigenetic Alterations In Slementioning
confidence: 99%